Effect of deposition current on bead geometry characteristics of low carbon steel single wall structure fabricated by wire arc additive manufacturing - Danny Wicaksono; Ario Sunar Baskoro; Nicholas Ego Guarsa; Gandjar Kiswanto; Syarif Junaidi (Universitas Muhammadiyah Magelang, 2025)
Wire arc additive manufacturing (WAAM) is gaining popularity due to its ability to produce large metal parts quickly and efficiently. It produces less waste and has a more efficient production time than subtractive manufacturing. However, those capabilities come with unavoidable disadvantages, post-processing by machining becomes necessary to achieve the desired product dimension. Therefore, this research aimed to evaluate the bead geometry and utilization area of the WAAM-fabricated structure by varying the deposition current. The wall-structured specimens were fabricated using gas metal arc welding (GMAW) with motorized drivers for x, y, and z coordinates. The material used in this research was low carbon steel ER70S-6 filler metal with ASTM A36 low carbon steel substrate. The Varying parameter was deposition current with other related process parameters remaining constant. Material testing and characterization techniques included geometric measurement by profile projector plotted into a scattered diagram, and the cross section of the specimens were observed using a digital microscope. The experiment resulted in increased bead dimension in width and height along with increased deposition current. The largest bead dimension was achieved in 180A deposition current with average bead width and height was 6.84 mm and 1.6 mm respectively. The best deposition current was 160A, with highest area utilization of 81.43% and width uniformity.